Penerapan Sikap Empati Konselor dalam Proses Konseling - Narti, Zulhelmi Narti; Hariko, Rezki; Karneli, Yeni (JAMBURA Guidance and Counseling Journal, 2023)
The process of counseling is a providing assistance carried out by a counselor to the counselee with the aim of alleviating the problems that are being felt by the counselee. In this case a counselor is required to have the ability to convince the counselee to follow the process counseling. One of the abilities that a counselor must have to achieve success in counseling is empathy. Where the attitude of the counselor's empathy is very important to build a good relationship with the counselee and is also the key to the success the process of counseling. The purpose of this research is to reveal the importance of applying counselor empathy in the process of counseling. The methodology used in this research is library research.